PUC Karnataka Science Class 12Department of Pre-University Education, Karnataka
Share

Books Shortlist

Solution for If Y = a X + B X 2 + C Then (2xy1 + Y)Y3 = (A) 3(Xy2 + Y1)Y2 (B) 3(Xy1 + Y2)Y2 (C) 3(Xy2 + Y1)Y1 (D) None of These - PUC Karnataka Science Class 12 - Mathematics

ConceptSimple Problems on Applications of Derivatives

Question

If $y = \frac{ax + b}{x^2 + c}$ then (2xy1 + y)y3 =

(a) 3(xy2 + y1)y2
(b) 3(xy1 + y2)y2
(c) 3(xy2 + y1)y1
(d) none of these

Solution

(a) 3(xy2 + y1)y2

Here,

$y = \frac{ax + b}{x^2 + c}$
$\Rightarrow \left( x^2 + c \right)y = ax + b$
$\text { Diffferentiating w . r . t . x, we get }$
$2xy + \left( x^2 + c \right)\frac{dy}{dx} = a$
$\text { Diffferentiating w . r . t . x, we get }$
$2y + 2x y_1 + 2x y_1 + \left( x^2 + c \right) y_2 = 0$
$\Rightarrow 2y + 4x y_1 + \left( x^2 + c \right) y_2 = 0$
$\text { Diffferentiating again w . r . t . x, we get }$
$2 y_1 + 4 y_1 + 4x y_2 + \left( x^2 + c \right) y_3 + 2x y_2 = 0$
$\Rightarrow 6 y_1 + 6x y_2 + \left( x^2 + c \right) y_3 = 0$
$\Rightarrow 6 y_1 + 6x y_2 + \left( \frac{- 2y - 4x y_1}{y_2} \right) y_3 = 0 \left[ \because 2y + 4x y_1 + \left( x^2 + c \right) y_2 = 0 \right]$
$\Rightarrow 6 y_1 y_2 + 6x \left( y_2 \right)^2 - 2y - 4x y_1 y_3 = 0$
$\Rightarrow 3 y_1 y_2 + 3x \left( y_2 \right)^2 - y - 2x y_1 y_3 = 0$
$\Rightarrow \left( y_1 + x y_2 \right)3 y_2 = \left( 2x y_1 + y \right) y_3$

Is there an error in this question or solution?

Video TutorialsVIEW ALL [1]

Solution If Y = a X + B X 2 + C Then (2xy1 + Y)Y3 = (A) 3(Xy2 + Y1)Y2 (B) 3(Xy1 + Y2)Y2 (C) 3(Xy2 + Y1)Y1 (D) None of These Concept: Simple Problems on Applications of Derivatives.
S